Study Of Combined Efficacy Of Upper Limb Proprioceptive Neuro Muscular Facilitation And Diaphragmatic Strengthening Exercise On Chest Expansion And Pulmonary Functionin Under Graduate Students With Rounded Shoulders - Uday Patil, Miss. Pratiksha; Naik, Gloria (Journal of Neonatal Surgery, 2025)
Background: One of the most prevalent postural issues among young adults who are otherwise asymptomatic is Rounded shoulders. A high prevalence of forward shoulder posture has been linked to sedentary lifestyles, inadequate postural adjustments, slouching, and extended flexed postures. The scapula opens, the pectoralis major muscle tightens, and the neck protrudes forward in the phenomenon known as rounded shoulder posture, resulting in When viewed from the side, the upper torso tilts forward and the shoulder rolls forward. The prevalence of rounded shoulders is 84% among young adults (18 – 24 years of age) Ethical clearance was obtained from Institution Ethical Committee. Total 52 participants were included in this study according to the inclusive criteria. This quasi-experimental study was conducted at D.Y. Patil College of Physiotherapy over 1.5 years. 52 students with rounded shoulders were recruited using convenience sampling. Participants underwent upper limb proprioceptive eneuromuscular facilitation and diaphragmatic strengthening exercise sessions for 8week 3session per week, and their pre and post chest expansion and vital capacity was evaluated using measuring tape and digital spirometery scores measured. Result: The paired t-test results indicate statistically significant improvements in various parameters post-intervention, as demonstrated by the p-values, all of which are <0.05. significantly difference found in chest expansion and vital capacity. And reduce the rounded shoulders. Conclusion: The study concludes that upper limb proprioceptive neuromuscular facilitation and diaphragmatic strengthening techniques on chest expansion and pulmonary function effectively reduce rounded shoulder in undergraduate students. of tubers (10.20 and 10.30 per plant), were recorded in plots having tuber treatment Terminila arjuna bark extract and two foliar sprays of Enviro (botanical virucides)followed by tuber treatment and six sprays with Tinospora cordifolia (aerial stem extract) and uber treatment and six foliar spray with Allium sativum (garlic clove extract) during 2022-23 and 2023-24, respectively.